Synthesis of Zeolite and Composite of Zeolite/TiO2 from Kaolin and Its Application to Adsorption-Photodegradation of Methylene Blue - Linda Trivana; Sri Sugiarti; Eti Rohaeti (UNIVERSITAS SEBELAS MARET (UNS), 2016)
In this study, zeolite was synthesized from kaolin which was founded from Bangka Belitung as the starting material. Meanwhile, sodium silicate was used as silica source. Zeolite is material with many benefits, such as become an adsorbent. Kaolin has been used as starting material due to high content of silica and alumina, i.e 35 - 50 %. Zeolite was prepared by hydrothermal synthesis process, by mixing the metakaolin which was produced by calcination of kaolin at 700 °C for 6 hours, with sodium silicate and NaOH. The NaOH was used to activate the major components of Si and Al in the kaolin.The hydrothermal process was conducted at 100 °C for 24 hours with various concentrations of NaOH, i.e 1.5 N and 2.5 N. The NaOH concentration might determine the type of zeolite obtained. To improve the nature as adsorbent, zeolites modified into zeolit/TiO2. The addition of TiO2into the prepared zeolit aimed to produce a material with capability as adsorbent-photocatalyst. The result of research found that the addition of NaOH 1.5 N produced zeolite NaP1. Meanwhile, the addition of NaOH 2.5 N produced the NaP1 zeolite, zeolite X, and faujasite. The composite of zeolit/TiO2has ability on adsorption-photocatalytic as it was proven by methylene blue degradation under ultraviolet light.